The miraculous - Redman, Jess, 1986- (Square Fish/Farrar, Straus and Giroux, 2020)
Eleven-year-old miracologist Wunder Ellis, records stories of miracles that happen, but when his baby sister dies just a few days after she is born, Wunder stops believing in miracles. He then meets a mysterious old woman who needs help, and he begins to see the miracles in everyday life again.